Acceptability of rubber dam placement by pediatric patients treated for pulpotymy in U.P. College of Dentistry, 2nd Semester, 2011-2012 - Cas Daisy Jane V.; Pardo, Janelle D.; Dimanlig, Anna Marie C.; Santos, Jessica K. Rebueno
Thesis (Doctor of Dental Medicine)--University of the Philippines Manila.
Introduction. Rubber dam placement (RDP) is universally accepted as a standard of care in peododontics but it is not commonly used. One of the reasons for its non use is the patient's unacceptability of the procedure. This study sought to confirm this reason by paying attention to the subjective feelings of the child every time rubber dam and its paraphernalia are placed on her/him.
Methods. The study involved 12 pediatric patients aged 5-7 years old. The participants' age, sex, tooth involved, amount of tooth destruction and working time were recorded. Their anxiety levels at baseline and during RDP were observed using Venham's Scale. They were also asked how they felt after every RDP procedure using Face Image Scale, and asked what is/are the features of specific rubber dam armamentaria that was least and most acceptable to them. Lastly, they were asked of their willingness to undergo RPD again.
Results. Based on Venham's Scale, there is a significant change in anxiety between each interval in RDP (α=.5, p=<.1): the lowest anxiety score was during baseline and the highest during clamp placement. Anxiety is not affected by the tooth involved (α=.05, p=2), amount of tooth destruction (α=.05, p=2), and the working time. Based on the the Face Image Scale (FIS), the most favorable rubber dam armamentaria are the rubber dam puncher and clamp holder (75%, FIS=5). The least favorable is the rubber dam clamp (33.33%, FIS=3). The most favorable is "color" while the least favorable is "nothing." Pediatric patients are willing to undergo RDA in the future (100%).
Conclusion. Despite increase in anxiety level of pediatric patients and regardless of tooth involved, amount of tooth destruction and working time, rubber dam placement is still acceptable for pediatric patients.
Keywords: Children--Dental care; Dams (Dentistry).; Rubber dam placement